Hubungan antara Dukungan Sosial dengan Kebahagiaan pada Dewasa Awal yang Mengalami Quarter Life Crisis - Silvianti, Aulia Dwi; Ramadhani, Ayunda; Rahayu, Diah; Rahman, Nadya Novia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Young adults need social support to achieve happiness and prevent self-isolation during the quarter-life crisis phase. This study examines the relationship between social support and happiness in young adults experiencing a quarter-life crisis using a quantitative approach. The sample, consisting of 209 participants, was selected through purposive sampling and screening methods that met specific criteria. The research utilized a happiness scale and a social support scale, with validity tests confirming that no items were excluded. Data analysis using Kendall’s Tau correlation test resulted in 0.359 > r-table 0.114 and a significance value of 0.000 (p < 0.05), indicating a positive relationship between friendship quality and happiness in young adults facing a quarter-life crisis. These findings suggest that higher social support correlates with greater happiness, whereas lower social support corresponds to lower happiness levels.